Identification of differentially expressed genes associated with ferroptosis in ulcerative colitis - Fang Zhang; Xin Jiang; Xuyu Chen; Zheng Wang; Jianlei Xia; Bingcheng Wang; Mei Wang; Yanbing Ding (PLoS ONE, 2025)
Purpose To identify ferroptosis-related genes associated with the development of Ulcerative colitis (UC), through bioinformatics and basic experiments. Methods Ferroptosis-related genes were identified from UC microarray data extracted from the GEO database and FerrDb. GO and KEGG pathway enrichment analyses were performed. Hub genes were identified through PPI analysis, leading to TF-hub gene and miRNA-hub gene regulatory network, predicting potential drug candidates by DSigDB. RT-qPCR, WB and IHC were employed to validate hub gene expression in animal samples. Clinical samples were gathered from Normal examiners and UC patients and IHC was performed to verify SLC7A5. Results Eleven ferroptosis-related DEGs were identified (nine upregulated and two downregulated genes) in UC, with eight genes chosen from the PPI network. MCC algorithm demonstrated that SLC7A11, PSAT1, SLC7A5, ACSF2, and ACSL4 were hub genes, predicting TFs, miRNAs and drugs. RT-qPCR confirmed significant differential expression of SLC7A5, ACSL4, and ACSF2. WB and IHC of mouse samples, as well as IHC of clinical samples, revealed significantly elevated SLC7A5 expression in the UC group compared to controls. Conclusion SLC7A5 emerged as a potential focus for understanding UC pathogenesis, potentially influencing ferroptosis. FOXP3, STAT6, and hsa-miR-186-5p are implicated in UC and ferroptosis, with minocycline identified as a potential treatment by inhibiting ferroptosis.